Randomized double-blind comparison trial among i-gel™, LMA-ProSeal™ and tracheal intubation with manual in-line stabilization in patients with simulated cervical spine movement limitation by rigid cervical collar immobilization - Chularojmontri, Tee; Engsusophon, Phatthanaphol; Deeprasertvit, Pichaya (Chulalongkorn Medical Journal, 2023)
Background : Tracheal intubation with manual in-line stabilization (TT-MILS) is the standard management in patients with cervical spine injury. The procedure of which is not practical for inexperienced personnel. Supraglottic airway device has a role in difficult airway management and been proved to be easy for new users. It may be effective for airway management in the setting of limited cervical spine movement. Objective : To compare airway management by i-gel, LMA-ProSeal™ and TT-MILS in anesthetized, paralyzed patients with simulated difficult airway by rigid cervical collar. Research design : A randomized, double-blind comparison study. Setting : In the operating rooms and surgical wards, King Chulalongkorn Memorial Hospital, a tertiary hospital with 1500 beds. Materials and Methods : Sixty patients scheduled for superficial surgery which required general anesthesia were recruited and randomized into three groups as follows, i-gel, LMA-ProSeal™ and TT-MILS. The patients and assessors were blinded. Primary outcome was the time to successful ventilation. Other measurements were insertion attempts, positive leak pressure, fiber optic-assessed glottic view, intraoperative and postoperative complications. Results : Twenty patients were assigned to each groups. Times to successful ventilation were not statistically different (i-gel 43.01 ± 26.94 s; LMA-ProSeal™ 50.05 ± 45.73 s; TT-MILS 68.43 ± 46.69 s; P = 0.113). The success rate for i-gel was 90% in the first attempt and 10% in second attempt vs. that of LMA-ProSeal™ which was 95% in the first attempt and 5% in the second attempt (P = 0.536). The positive leak pressure was significantly higher in LMA-ProSeal™ group than that of in the i-gel group (25.55 ± 3.01 cmH2O vs. 23.35 ± 3.31 cmH2O; P = 0.035). The glottic views were not statistically different between the groups. The incidences of sore throat and odynophagia were significantly lower in the i-gel and LMA-ProSeal™ groups, compared to that of the TT-MILS group (P = 0.000, 0.017 respectively). Conclusion : I-gel had shorter insertion time compared to LMA-Proseal™ and TT-MILS. Regarding the less seal, i-gel might be a reasonable alternative to the LMA-Proseal™ and TT-MILS in patients with reduced neck movement and limited mouth opening.